Technical Features, Feasibility, and Acceptability of Augmented Telerehabilitation in Post-stroke Aphasia—Experiences From a Randomized Controlled Trial - Øra, Hege Prag; Kirmess, Melanie; Brady, Marian C.; Sørli, Hilde; Becker, Frank (Frontiers in Neurology, 2020)
Background: Post stroke aphasia is a communication disorder where existing evidence favours intensive therapy methods. Telerehabilitation represents a service model for geographically remote settings, or other barriers to clinic attendance or to facilitate an augmentation of therapy across a continuum of care. Evidence to support efficiency, feasibility and acceptability is however still scarce. Appraising aphasia telerehabilitation in controlled trials beyond its effectiveness, by investigating feasibility and acceptability, may facilitate implementation into clinical practice. Methods: In our pilot randomized control trial we investigated the feasibility and acceptability of speech and language therapy by videoconference, in addition to usual care, in people with aphasia following stroke. To improve functional, expressive language a tailored intervention was given one hour per day, five times per week over four consecutive weeks. Feasibility measures included evaluation of technical setup using diary logs. Acceptability was investigated by examining adherence and satisfaction with therapy alongside evaluation of data safety and privacy. Results: Feasibility and acceptability data were collected in relation to 556.5 hours of telerehabilitation delivered to 30 participants over a two-year intervention period by 3 speech-language pathologists. Protocol adherence was high, with a tolerable technical fault rate; 86 faults were registered over 541 video sessions. Most (80%; n=30) of the participants experienced zero to three faults. The main cause of technical failures was flawed internet connection, causing delayed or interrupted therapy. Total satisfaction with telerehabilitation was rated good or very good by 93.1 % (n=29) of participants and two of three speech-language pathologists. Within a moderate variance of technical failure, participants experiencing more faults were more satisfied. No serious events regarding security and privacy were reported. Our model is feasible and ready to be implemented across a range of clinical settings and contexts. Conclusions: Synchronous telerehabilitation for post stroke aphasia is feasible, acceptable and shows tolerable technical fault rates with high satisfaction amongst patients and pathologists. Within a low rate of faults, satisfaction was not negatively influenced by fault frequency. Access to clinical and technical expertise is needed when developing telerehabilitation services. Telerehabilitation may be a viable service delivery model for aphasia rehabilitation.